Highly syntenic regions in the genomes of soybean, Medicago truncatula, and Arabidopsis thaliana - Mudge, Joann (BioMed Central, 2005)
BACKGROUND: Recent genome sequencing enables mega-base scale comparisons between related genomes. Comparisons between animals, plants, fungi, and bacteria demonstrate extensive synteny tempered by rearrangements. Within the legume plant family, glimpses of synteny have also been observed. Characterizing syntenic relationships in legumes is important in transferring knowledge from model legumes to crops that are important sources of protein, fixed nitrogen, and health-promoting compounds. RESULTS: We have uncovered two large soybean regions exhibiting synteny with M. truncatula and with a network of segmentally duplicated regions in Arabidopsis. In all, syntenic regions comprise over 500 predicted genes spanning 3 Mb. Up to 75% of soybean genes are colinear with M. truncatula, including one region in which 33 of 35 soybean predicted genes with database support are colinear to M. truncatula. In some regions, 60% of soybean genes share colinearity with a network of A. thaliana duplications. One region is especially interesting because this 500 kbp segment of soybean is syntenic to two paralogous regions in M. truncatula on different chromosomes. Phylogenetic analysis of individual genes within these regions demonstrates that one is orthologous to the soybean region, with which it also shows substantially denser synteny and significantly lower levels of synonymous nucleotide substitutions. The other M. truncatula region is inferred to be paralogous, presumably resulting from a duplication event preceding speciation. CONCLUSION: The presence of well-defined M. truncatula segments showing orthologous and paralogous relationships with soybean allows us to explore the evolution of contiguous genomic regions in the context of ancient genome duplication and speciation events.